(untitled) (International Journal of Economics Management and Social Science, 2026)
This study examines the intersection of rural development initiatives in Indonesia with global sustainability challenges, particularly focusing on digital inclusion and climate adaptation strategies. Through a qualitative library research approach, this paper analyzes how Indonesian villages are navigating the dual pressures of technological advancement and environmental vulnerability while pursuing sustainable development goals. The research reveals that while Indonesia has made significant progress in rural infrastructure development, persistent challenges remain in achieving equitable digital access and building climate-resilient communities. The findings demonstrate that successful rural development in Indonesia requires an integrated approach that addresses both global technological trends and local environmental realities. The study contributes to understanding how developing nations can leverage technology for rural advancement while maintaining environmental sustainability and cultural preservation. Key findings indicate that community-based approaches, combined with government policy support and international cooperation, are essential for creating sustainable rural development models that can serve as examples for other developing regions facing similar challenges. Keywords: rural development, digital divide, climate resilience, sustainable development, Indonesia, global challenges